Proceedings of the 2018 Advances In Motility and In NeuroGastroenterology: AIMING for the Future Single Topic Symposium. Issue 2 (August 2020) - Ambartsumyan, Lusine; Khlevner, Julie; Nurko, Samuel; Rosen, Rachel; Kaul, Ajay; Pandolfino, John E.; Ratcliffe, Elyanne; Yacob, Desale; Li, B.U.K.; Punati, Jaya; Sood, Manu; Rao, Satish S.C.; et al.
ABSTRACT: Objectives: Motility and functional disorders are common in children and often debilitating, yet these disorders remain challenging to treat effectively. At the 2018 Annual North American Society for Pediatric Gastroenterology, Hepatology and Nutrition meeting, the Neurogastroenterology and Motility Committee held a full day symposium entitled, 2018 Advances In Motility and In NeuroGastroenterology – AIMING for the future. The symposium aimed to explore clinical paradigms in pediatric gastrointestinal motility disorders and provided a foundation for advancing new scientific and therapeutic research strategies. Methods: The symposium brought together leading experts throughout North America to review the state of the art in the diagnosis and management of motility and functional disorders in children. Presentations were divided into esophageal, antral duodenal, and colorectal modules. Each module included oral presentations by experts in the respective fields, leading to thought-provoking discussions. There were 2 breakout sessions with small group discussions on select topics, focusing on defining scientific insights into the diagnosis and management of pediatric functional gastrointestinal and motility disorders in a systematic, segment-based approach. Conclusions: The field of neurogastroenterology has made remarkable progress in the last decade. The current report summarizes the major learning points from the symposium highlighting the diagnosis and promising therapies on the horizon for pediatric neurogastrointestinal and motility disorders.